Miller: all about Japanese (a review of a review) - Benedict, Paul K. (2024)
Twenty years ago my first book, the Sino-Tibetan: a Conspectus (SIT.). appeared, with Jim Matisoff as contributing editor. The Sino-Tibetan field was even more esoteric in those days than at present and I feared the worst: few would read the book and even fewer appreciate it. I was hardly prepared for what followed, however. Roy Andrew Miller (hereafter RAM) reviewed STC at great length: more accurately, he wrote a 'review' article containing a great number of words, German as well as English.' He found absolutely nothing good about the book, not even (as Matisoff has observed) the paper on which it was printed. He made it all somehow seem to be a vast conspiracy against linguistic scholarship. the product of a collegiality of oligophrenics. Who in the world would read the book, let alone buy it?